A correlative study between the microstructure and electrical properties of lead-free piezoceramics (1-x)BHT-xYLG driven by the synergistic action of multiple factors. Issue 11 (September 2022) - Cai, Enpei; Liu, Qibin
Abstract: Piezoceramics are important functional materials with broad applications in electronics, communication, medicine, and energy. Increasing environmental protection and human health concerns about the toxicity of lead have impelled the development of lead-free piezoceramics. At this work, in combination with phase field simulation, grain growth mechanism, ferroelectric domain wall model, and defect dipole formation mechanism, (1- x )Ba(Hf0.02 Ti0.98 )O3 - x (Y0.5 Li0.5 )GeO3 [(1- x )BHT- x YLG, x  = 0–0.40 mol%] lead-free piezoceramics were designed and fabricated via the two-step synthesis and solid-state reaction method, which yielded superior comprehensive electrical property. Phase field simulation respectively simulates the distribution of ferroelectric domains of O and T phase under different external electric fields (0–20 kV/mm) and the phase states under different temperatures (−100 to 150 °C). This research finds that their electrical properties are affected by the synergistic action of multiple factors, e.g., orthorhombic-tetragonal phase boundary (O-T PB), grain size (GS), domain-wall (DW), and defect dipole (DD), etc., rather than any single factor. Highlights: Excellent ferroelectric properties are obtained at x  = 0.08 mol%. O-T phase boundary is successfully constructed at RT for all samples. Phase field simulation is in good agreement with the experimental results. Electrical properties are affected by the synergistic action of multiple factors.